Glycemic Control Improvement amongst Patients with Diabetes Mellitus during a COVID-19 Lockdown in Jordan - Nofal, Amani; Abu Jabeh, Raghed; Alrafayia, Dana; Hyasat, Tala; Suboh, Lojayn; Aljabiri, Reyad; Al Ryalat, Saif; Alhawari, Hussam; Jaber, Ruba (Jordan Medical Journal, 2023)
Aims: The purpose of this study is to evaluate the effects of lockdown measures by the Jordanian government to contain the spread of the novel corona virus (COVID-19) on glycemic control of patients with diabetes mellitus. Methods: This cross-sectional study was conducted in Jordan University Hospital. A total of 264 patients with type 2 or type 1 diabetes mellitus were sampled. The authors evaluated the extent of glycemic control reached by patients with type 2 or type 1 diabetes mellitus by measuring change in glycosylated hemoglobin (A1C) values, in addition to the number of hypoglycemic episodes experienced by patients during lockdown. The authors conducted a questionnaire via telephone interviews to record information about drug adherence and availability, diet, physical activity, and telephone consultations. A paired sample t-test was used to compare values before and after lockdown. Results: A significant reduction in HbA1C values was found during lockdown (p=0.038), with only 33.6% of patients experiencing one or more hypoglycemic episodes; both factors suggest controlled blood glucose levels. Medication adherence was found to be the main reason for improvement, with 74.8% of our population being strongly adherent to their medications. Conclusions: In Jordanian patients with diabetes mellitus, glycemic control was significantly improved during COVID-19 lockdown and this was found to be associated with strong medication adherence.